Sumber Daya Manusia dalam Mewujudkan Halal Entrepreneurship di Indonesia - Moch Mahsun; Nur Asnawi; Muhammad Djakfar; Salim Al Idrus; Fauzan Almanshur (Idarotuna : Journal of Administrative Science, 2022)
Entrepreneurship is the thing that contributes the most to world economic development, especially in developing countries such as Indonesia. One of the most popular is halal entrepreneurship today. Indonesia itself is targeting the vision of becoming a global halal hub in the world in 2024. For Indonesia it is not an easy matter to realize this vision, this is because it is experiencing obstacles from the Usaha Mikro, Kecil dan Menengah sector which is still a lot of obstacles in the process of providing halal assurance and The readiness of human resources is still few who are aware of the importance of halal products. This research contributes more specifically to the discussion of human resources who are aware of the halal assurance required and in accordance with Islamic provisions, as well as formulating human resources as the main capital in Halal entrepreneurship.